Environmental Visibility Study In The Construction Of Simple Houses In Bangkalan District, Madura, East Java - Helsa Ade Ayu Kumala Putri; Andi Patriadi; Sajiyo Sajiyo (Syntax Corporation Indonesia, 2025)
The poverty line per household illustrates the minimum rupiah amount required by an average poor household to meet their basic needs and avoid poverty classification. Simple housing development remains a critical issue in regional development planning, particularly in low-income areas. Bangkalan Regency, East Java, faces challenges such as limited infrastructure and socio-economic disparities, which hinder the provision of affordable and adequate housing. This study employs Neighborhood Visibility Analysis to evaluate the environmental accessibility, affordability, and livability of simple housing in the region. Six key variables were identified as determinants of visibility: disaster resilience, land use efficiency, energy efficiency, adequate living space, access to public spaces, and effective waste management. The results reveal a significant gap between community expectations and reality, particularly regarding environmental quality, affordability, and infrastructure. These findings underscore the necessity of integrating environmental visibility into housing policies to ensure sustainability and meet the needs of low-income populations. The study also highlights the role of government and developers in bridging these gaps by adopting sustainable practices and addressing community needs. Future research should expand the scope of visibility analysis, incorporating broader socio-economic and environmental variables, to validate and enhance these findings. This approach is vital to supporting sustainable development goals and improving the quality of life for residents in low-income communities